Ellipsoidal protrusions for enhanced thermal performance in fin-tube heat exchangers - Mun Su Lee; Jeong Geun Gwon; Young Min Seo; Hoon Ki Choi; Yong Gap Park (Case Studies in Thermal Engineering)
Enhancing heat transfer in fin-tube heat exchangers is crucial for improving energy efficiency across various industrial applications. In this study, the effects of the position angle (α), attack angle (β), and size scale (ε) of ellipsoidal protrusions on the heat transfer characteristics of a fin-tube heat exchanger were numerically analyzed within the Reynolds number range of 1500–5000. Results showed that as α and ε increased, the vorticity generated downstream of the protrusions also increased. At α = 45°, heat transfer decreased as β increased, whereas at α = 67.5° and 90°, it increased with β. The Colburn j factor of fins with protrusions increased by 48.85 % compared to that of fins without protrusions at α = 90° and β = 40° with ε = 1.2. At α = 90°, both the Colburn j factor and the friction factor increased significantly; thus, the optimal position was identified as α = 67.5° and β = 40° with ε = 1.2, where the volume goodness factor was 25.41 % higher than that of fins without protrusions. These findings offer valuable insights for designing more efficient fin-tube heat exchangers, with implications for energy conservation in thermal management systems.